2016
DOI: 10.1111/1748-5967.12164
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing, de novo assembly, and functional annotation of an endangered Nymphalid butterfly, Fabriciana nerippeFelder, 1862

Abstract: Grassland butterflies are considered representative indicators of biodiversity and ecosystem health. Their dramatic decline caused by habitat destruction, intensifying agriculture and global warming has prompted concern for conservation. While ecological indices of butterflies have been documented, there is a lack of genomic resources relative to the biological importance of this group. Here, we report, first whole-transcriptomic resource for Fabriciana nerippe, a brush-footed butterfly member that is endanger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 62 publications
(88 reference statements)
1
10
0
Order By: Relevance
“…3 ). This GO term distribution is congruent with other insect transcriptomes already sequenced ( Hwang et al., 2016 ).…”
Section: Resultssupporting
confidence: 87%
“…3 ). This GO term distribution is congruent with other insect transcriptomes already sequenced ( Hwang et al., 2016 ).…”
Section: Resultssupporting
confidence: 87%
“…The locally curated PANM-DB was an addition to the Molluscs database, and covers the available sequences of the Protostomia group in a multi-FASTA format [53]. Furthermore, our results showed that more than 90% of unigenes with a sequence length >2000 bp matched with a homologous protein in the databases, which is possible because the protein-coding genes generally give rise to longer full-length transcripts [54]. The BLASTX top-hit species distribution showed putative homology of the annotated unigene sequences across species in the PANM-DB.…”
Section: Discussionmentioning
confidence: 99%
“…PANM‐DB is the database of choice for sequence annotation of insect and molluscan non‐model species (Hwang et al . 2016; Kang et al . 2018; Patnaik et al .…”
Section: Resultsmentioning
confidence: 99%
“…The result obtained confirms that annotation using PANM-DB is more efficient with greater number of valuable annotations compared to other public databases. PANM-DB is the database of choice for sequence annotation of insect and molluscan non-model species (Hwang et al 2016;Kang et al 2018;Patnaik et al 2016aPatnaik et al , 2016bPatnaik et al 2019). In the annotated results, the highest number of unigenes (6,875 sequences) found homologous sequences exclusively in PANM-DB, whereas about 10,983 unigenes were found annotated to all the four databases.…”
Section: Sequence Annotation Of Unigenesmentioning
confidence: 99%